Evolving Arctic Security Architecture Towards a Cooperative One - Uğur, Mehmet Ali; Dal, Adnan (Uluslararası Politika ve Güvenlik Çalışmaları Derneği (INTPOLSEC), 2021)
Ever since it emerged as another remote Cold War battlefield, the discourse regarding Arctic security has gone through a considerable change in both scope and depth. While this inhospitable environment was once only assessed as a rather insignificant element of the national security and sovereignty calculations of the two blocs throughout the Cold War era, such traditional perception of state-level relations has been shifting to a different plane in recent decades. This article examines the nature of this transforming security architecture of the Arctic from a competitive to a cooperative one in the last three decades. It goes on to evaluate the ‘broad security perception’ from the lens of three significant initiatives: the Murmansk Speech, the intended mandate of the Arctic Council, and economic development priorities spelled out by all Arctic states in their national strategies pertaining to the Arctic. The study, thus, concludes that unlike classical security formulations of the Cold War years, an enhanced and all-inclusive cooperative security concept will eventually pave the way for a solid and sustainable region-wide regime as societal, environmental, human, and economic security concerns have been escalating to the top of the priority list in the region alongside with national security perceptions of states.

Soğuk Savaş’ın çatışma alanlarından biri haline geldiğinden beri Arktik Bölgesi’nin güvenliği ile ilgili tartışmalar hem kapsam hem de derinlik açısından önemli bir değişim geçirmiştir. Sert iklim koşullarına sahip söz konusu bölge Soğuk Savaş dönemi boyunca bloklararasında daha çok ulusal güvenlik ve egemenliğin önemsiz bir unsuru olarak değerlendirilirken, son yıllarda devlet düzeyindeki ilişkilerde görülen bu geleneksel algı farklı bir aşamaya evrilmektedir. Bu çalışma, son yıllarda Arktika’da söz konusu güvenlik yapısının rekabetten işbirliğine doğru evrilen doğasını incelemektedir. Çalışmada Murmansk Demeci, Arktik Konseyi’nin yetkisi ve Arktik devletlerinin Arktika ile ilgili ulusal strateji belgelerinde yer alan ekonomik kalkınma öncelikleri gibi üç önemli girişim odağı sayesinde bölgedeki geniş güvenlik algılaması değerlendirilmektedir. Bu nedenle çalışma, Soğuk Savaş yıllarındaki klasik güvenlik formülasyonlarının aksine bölgede devletlerin ulusal güvenlik algılamalarının yanı sıra toplumsal, çevresel, insani ve ekonomik güvenlik kaygılarının öncelikli olarak ele alınmasıyla birlikte genişletilmiş ve tüm yönleriyle kapsayıcı ortak güvenlik kavramının bölge çapında somut ve sürdürülebilir bir rejime yol açacağı iddiası ile nihayete erdirilmektedir
Evolving Arctic Security Architecture Towards a Cooperative One
Keywords: International Relations; Uluslararası İlişkiler